INTRODUCTION AND EVALUATION PROBLEM OF BPM AND RPA APPROACHES IN MODERN LOGISTIC SYSTEMS - Uskenbayeva, Raissa; Nalgozhina, Nurgul; Berkaliyeva, Moldir (Scientific Journal of Astana IT University, 2022)
Every modern business system tends to a reduction of production and management costs. There are many ways of upgrading and automatization however most common is introducing Business Process Management. Although BPM is a holistic approach to optimizing and automating business processes from start to finish, this article represents Robotic Process Automation as a new form of workflow automation technology. From the construction of a consistent overview that allow the comparative analysis of the methodologies, to select the one that suits better its specificities it can be verified that, although they share the same objective, each notation has its specific characteristics. According to those representational analyses, the introduction methodology of the robotic solution technique is represented within the framework of a logistic business process. The author provides the work with a detailed description of BPM and RPA models integration highlighting their main features. Along with that, the literature analysis was conducted to define the problems of the logistic business automatization’s current condition. The paper is a consequent comparison of BPM and RPA, especially in logistic systems. The author provides methodological recommendations on the adoption of management and automation tools in logistic systems.